Morphological aspects of the implant-bone interface in the long postoperative periodafter implantation - Міщенко, Олег Миколайович; Любчак, Ірина Володимирівна; Олешко, Олександр Миколайович; Погорєлов, Максим Володимирович (Actual Dentistry, 2019)
Summary. Of the many constituent aspects of the success of implantation, osseointegration is perhaps the most important and in itself depends on several factors, including the biomedical characteristics of the implant, the ability to protect against adjacent tissue stress and the longevity of functioning after implantation. To date, there is an insufficient number of results of an objective assessment of the implant-bone interface in vivo in the long term functioning of the implant in humans. Objective: to study the morphological aspects of the implant-bone interface in the long-term functioning of dental implants of various alloys. Materials and methods. Due to the failure of the orthopedic design or due to the failure of the structural elements of the superstructure, if it is impossible to repair, the implants were removed, followed by augmentation to the area of the resulting defect. We studied dental implants from titanium alloy (Grade5) – 7.6 ± 1.5 years after installation (3 cases), zirconium (KTZ-125) – 5.7 ± 1.9 (4 cases), betta-titanium-zirconium alloy – 6.2 ± 2.6 years after installation (3 cases). After extraction, the implant bone interface was studied by scanning electron microscopy with energy dispersive analysis and histology with hematoxylin- eosin staining. Results. Implant / bone interface status in remote structures of various compositions has shown the advantage of beta-titanium-zirconium alloy over Grade5 and KTZ 125. The number of observations does not allow to reveal a reliable dependence of the interface structure on different implant geometry, but a decrease in the number of bone microcracks and the absence of connective tissue may indicate the advantage of a rotation parabola. Key words: morphological aspects of the implant-bone interface, energy dispersive analysis, implant.